2012
DOI: 10.1177/0363546512469089
|View full text |Cite
|
Sign up to set email alerts
|

Cannulated Screw Fixation of Refractory Olecranon Stress Fractures With and Without Associated Injuries Allows a Return to Baseball

Abstract: Open reduction and internal fixation of olecranon stress fractures in competitive baseball players has a high rate of success in returning players to or above their former level of play and allows for good elbow function at an average of 6.2 years postoperatively. However, these patients are at high risk for additional future surgeries on their throwing arm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…Titanium implants are preferred in case postoperative MRI is considered. Paci et al [67] reported particularly good outcomes and a high rate of success using screw fixation for refractory olecranon stress fractures in a series of 18 baseball athletes. Players were able to return to sport and perform at or above their former level of activity.…”
Section: Epidemiologymentioning
confidence: 98%
See 2 more Smart Citations
“…Titanium implants are preferred in case postoperative MRI is considered. Paci et al [67] reported particularly good outcomes and a high rate of success using screw fixation for refractory olecranon stress fractures in a series of 18 baseball athletes. Players were able to return to sport and perform at or above their former level of activity.…”
Section: Epidemiologymentioning
confidence: 98%
“…Olecranon stress fractures (OSF) remain rare even in the athlete population. Athletes at risk include gymnasts and athletes who engage in overhead activities, like baseball players, javelin throwers, and weight lifters [67]. Characteristics of olecranon stress fractures are largely dependent on the age of patients and, even more so, the status of the physis.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…15 Transverse fractures are more likely to result from repetitive triceps strain (ie, from weightlifting), whereas oblique fractures are more likely to result from valgus overload (ie, from throwing). Occasionally, fragmentation or sclerosis may also be noted, and films should be compared with the contralateral, unaffected side.…”
Section: Posterior Elbow Injuries Olecranon Apophysitis/stress Fracturementioning
confidence: 99%
“…Treatment for proximal ulna stress fractures includes both nonsurgical 24 and surgical 25 options. According to the general treatment principles of stress fractures, treatment starts nonoperatively with cessation of sports activities and active rest.…”
Section: Proximal Ulnar (Stress) Fracturesmentioning
confidence: 99%